2019
DOI: 10.1039/c8bm01664j
|View full text |Cite
|
Sign up to set email alerts
|

Bulk poly(N-isopropylacrylamide) (PNIPAAm) thermoresponsive cell culture platform: toward a new horizon in cell sheet engineering

Abstract: In contrast to the conventional ‘grafting’-based thermoresponsive cell culture platform, we first developed a bulk form of thermoresponsive cell culture platform for attaching/detaching diverse types and origins of the cell sheets in different shape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…PNIPAAm has been used for smart materials, which mainly utilizes surface property changes and volume phase transitions with response to ambient temperature. The versatility of PNIPAAm has led to finding uses in cell culture [4], tissue engineering [5], enzymatic immobilization [6], drug delivery [7], wound dressing [8], biosensors [9], etc. One of the most important applications of PNIPAAm is cell culture.…”
Section: Preparation Of Pnipaam Medicated Substrates For Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…PNIPAAm has been used for smart materials, which mainly utilizes surface property changes and volume phase transitions with response to ambient temperature. The versatility of PNIPAAm has led to finding uses in cell culture [4], tissue engineering [5], enzymatic immobilization [6], drug delivery [7], wound dressing [8], biosensors [9], etc. One of the most important applications of PNIPAAm is cell culture.…”
Section: Preparation Of Pnipaam Medicated Substrates For Cell Culturementioning
confidence: 99%
“…The permeable calcein-AM is enzymatically converted into calcein showing bright green fluorescence in the cytoplasm of viable cells, while ethidium homodimer can enter cells with compromised membranes and takes up red fluorescence upon binding to nucleic acids [114]. The ratio of fluorescence intensity of calcein AM to ethidium homodimer demonstrated the degree of cell viability [5,115].…”
Section: Cell Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For the Live/Dead staining, the cells were washed with PBS and treated with 4 × 10 −3 m calcein acetoxymethyl ester (green) and 2 × 10 −3 m ethidium homodimer‐1 (red) at 37 °C for 30 min. [ 32 ] In the case of phalloidin and DAPI staining, the cells were fixed with 4% paraformaldehyde at room temperature for 15 min, permeabilized with 0.2% Triton X‐100 in PBS at 4 °C for 15 min, and blocked with 1% BSA at room temperature for 1 h. Afterward, the cells were stained with TRITC‐conjugated phalloidin and DAPI at room temperature for 60 and 5 min, respectively. For each step, the cells were washed more than three times by PBS for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…For example, long exposure (more than 20 min) at outside of cell incubator with different temperature, CO 2 concentration, and humidity which can cause negative effect to cell function or viability is required to detach the cells from the PNIPAAm coated surface. 9,10 pH-sensitive property of synthetic material has been also applied for detaching cells without proteolytic cleavage. 11 It has been reported that changing pH condition of human mesenchymal stem cells, that cultured on pH-responsive CaCO 3 precipitated dish, induced cell sheets detachment.…”
Section: Introductionmentioning
confidence: 99%